THE ROLE OF MOBILE APPLICATIONS IN EDUCATING EARLY CHILDREN (International journal of artificial intelligence, 2025)
This article analyzes the possibilities of mobile applications in teaching young students, the issues of developing a teaching model that is appropriate for their psychological and pedagogical characteristics. The advantages of mobile educational technologies, their effective use in the educational process, as well as their role in developing independent thinking and interactive learning skills in students are scientifically substantiated.